Substrate augmented catalytic activity towards NRR: a case study of Li doped Al clusters on defective graphene - Samal, Pragnya Paramita; Poonam; Krishnamurty, Sailaja (2021)
Density Functional Theory (DFT) based methods are applied to examine the potential of lithium doped aluminium clusters consisting of 3-13 atoms for dinitmgen molecule activation in terms of N N bond length, redshift in N N bond stretching frequency, nitrogen interaction energy and frontier molecular orbitals analysis. The present work highlights the role of monovacant C-3 defective graphene as a support in fine tuning the catalytic activity of Li doped Al clusters for reduction of N-2. Fundamental insights to synergic binding of clusters with defective graphene is brought out and its role in enhancing activation of dinitmgen molecule is explained. Supported Aln-1Li clusters with six or more atoms are noted to be more active towards N-2 molecule activation as compared to the clusters without support. Dinitrogen molecule undergoes a maximum bond elongation of 1.56 angstrom corresponding to redshift of 1690 cm(-1) on Al7Li@graphene and Al12Li@graphene. This is maximum value reported in context of activation for N-2 molecule till date.
Keywords: Al clusters; Al12Li; C-3 defective graphene; DFT; Li Doping; N-2 activation; Red-shift

Sulfonated zinc phthalocyanine coating as an efficient and ecofriendly corrosion inhibitor for copper surfaces: an in silico led design and its experimental validation - Dekshinamoorthy, Amuthan; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Khatri, Praveen K.; Jain, Suman Lata; Ray, Anjan; Vijayaraghavan, Saranyan (Langmuir, 2023)
The current study highlights the successful integration of an in silico design with experimental validation to create a highly effective corrosion inhibitor for copper (Cu) surfaces. The synthesized sulfonated zinc phthalocyanine (Zn-Pc) is electrochemically characterized and demonstrates an impressive 97% inhibition efficiency, comparable to the widely used industrial corrosion inhibitor, BTA, for Cu surfaces. The corrosion inhibition is comprehensively analyzed through potentiodynamic polarization and impedance spectroscopy techniques, supported by their respective equivalent circuits. Furthermore, the sample undergoes thorough characterization using scanning electron microscopy, energy-dispersive X-ray analysis, X-ray photoelectron spectroscopy, contact angle measurements, and atomic force microscopy. Density functional theory calculations reveal that sulfonated Zn-Pc exhibits the highest interaction energy, underscoring its exceptional inhibition properties. These results open possibilities for utilizing computational methods to design and optimize corrosion inhibitors for protection of Cu surfaces.

Synergistic combination of ZnCl2/Cu-BTC MOF for the photocatalytic oxidative deamination of benzylamines using CO2 under visible-light irradiation - Kumar, Amod; Bhatt, Sakshi; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Jain, Suman L. (ACS Applied Engineering Materials, 2024)
This paper demonstrates the first CO2-mediated oxidative deamination of benzylamines to benzaldehydes using a combination of ZnCl2 and Cu-BTC MOF as photocatalysts in a carbon tetrachloride solvent under visible-light irradiation. Interestingly, the synergistic combination of ZnCl2 and Cu-BTC afforded the targeted oxidation of benzylamine to benzaldehyde, wherein CO2 acted as an oxidant. The individual components yielded the corresponding imine as the main product, resulting from the oxidative coupling of the benzylamine. DFT calculations and computational studies supported the proposed reaction pathways involving the formation of an intermediate imine from benzylamine via dehydrogenation followed by hydrolysis to produce benzaldehyde. This work, demonstrating the use of CO2 as an oxidant, may open up new avenues for CO2 utilization in chemical production by using sustainable light energy.

syn-Selective hydrosilylation and hydroboration of alkynes at room temperature catalyzed by a phosphine-free (NNN)Fe(ii) complex - Pradhan, Chandini; Dubey, Shivansh; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Catalysis Science & Technology, 2025)
Catalytic hydrofunctionalization of alkynes is the ideal and atom-economical route to synthesize vinylsilanes and vinylboronates, which are valuable organic building blocks. However, the process suffers from using expensive phosphine-ligated catalysts, sensitive organometallic activators, and elevated reaction temperatures. To overcome these challenges, herein, we developed a series of phosphine-free (NNN)-ligated iron complexes and demonstrated their potential as efficient catalysts for the hydrosilylation and hydroboration of both internal and terminal alkynes using NaOtBu as an activator. The reactions proceeded smoothly using 1.5 mol% catalyst loading at room temperature and provided syn-selective vinylsilanes and vinylboronates. This hydrofunctionalization exclusively delivered mono-silylated and mono-borylated vinyls with tolerance of sensitive functionalities. At the same time, terminal alkynes provided excellent anti-Markovnikov selectivity with thermodynamically feasible beta-(E)-vinylsilanes and beta-(E)-vinylboronates. The presence of an N-H moiety in the ligand backbone is crucial in generating an Fe(ii) active catalyst and facilitating the catalytic process. Mechanistic investigations, including controlled reactions and external additive experiments, were performed to propose a redox-neutral reaction mechanism with iron maintaining its +2 oxidation state throughout the cycle. The DFT energy calculations unanimously support the proposed reaction mechanism.